2013
DOI: 10.1080/03601234.2013.730299
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of aSphingomonassp. strain F-7 degrading fenvalerate and its use in bioremediation of contaminated soil

Abstract: A fenvalerate-degrading bacterial strain F-7 was isolated from long-term contaminated sludge. Based on morphological, physiological and biochemical characterization, and phylogenetic analysis of 16S rRNA gene sequence, strain F-7 was identified as Sphingomonas sp. The bacterium could utilize fenvalerate as the sole source of carbon. An amount measuring 100 mg L(-1) fenvalerate was completely degraded within 72 h and 3-phenoxybenzoic acid (3-PBA) was detected as a major metabolite. The result indicates that S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…The extracts were analyzed at an injection temperature of 250 C and EI source temperature of 280 C. The extract volume was 1 mL, and the sample was injected into the column with a temperature program of 90 C (2 min), 6 C min ¡1 to 150 C (1 min), 10 C min ¡1 to 180 C (4 min), and 20 C min ¡1 to 260 C (10 min). Metabolites were identified and quantified based on the retention times and peak areas of the pure standards [16].…”
Section: Isolation and Identification Of Fenvalerate Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts were analyzed at an injection temperature of 250 C and EI source temperature of 280 C. The extract volume was 1 mL, and the sample was injected into the column with a temperature program of 90 C (2 min), 6 C min ¡1 to 150 C (1 min), 10 C min ¡1 to 180 C (4 min), and 20 C min ¡1 to 260 C (10 min). Metabolites were identified and quantified based on the retention times and peak areas of the pure standards [16].…”
Section: Isolation and Identification Of Fenvalerate Metabolitesmentioning
confidence: 99%
“…However, little information is available concerning the biodegradation of fenvalerate [9,15] and its degradation pathway. Yu et al [16] reported that Sphingomonas sp. F-7 was capable of completely degrading 100 mg L ¡1 fenvalerate within 72 h and 3-phenoxybenzoic acid (3-PBA) was detected as a major metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of experiment, no metabolite was detected by GC/MS indicating that the metabolite compounds could be further transformed and metabolized. Similar biodegradation pathways have been reported for other pyrethroids such as cypermethrin [14,28], cyfluthrin [9,23], and fenvalerate [15,33]. It could be inferred that ester hydrolysis by carboxylesterases may be the major biodegradation pathway of pyrethroids in microorganism.…”
Section: Analysis Of Fenpropathrin Biodegradation Metabolitesmentioning
confidence: 53%
“…Whereas, 44.4 mg kg −1 of fenvalerate was removed from fresh soil inoculated with strain F-7. It is noteworthy that fenvalerate degradation was faster in nonsterilized soils than in sterilized soils indicating a contribution of indigenous flora to fenvalerate removal (Yu et al 2013).…”
Section: Bacterial Degradation Of Pyrethroid Pesticidesmentioning
confidence: 99%